Analysis of Patient Satisfaction With The Use of The Jkn Mobile Application At Godong Community Health Center - Fadhilah, Isnaini Qoriatul; Masrochah, Siti; Lestari, Sri; Kusdianto, Eko Teguh (Procedia of Engineering and Life Science, 2024)
BPJS Health implements a digital transformation in the form of the JKN mobile application. The JKN mobile application is expected to provide easy access and more optimal service for participants. The JKN Mobile Application is expected to simplify the registration process and improve the quality of health services [1]. A preliminary survey at the Godong 1 Health Center registration regarding the use of the Mobile JKN application was carried out in February 2023 on 10 BPJS Health patients, 5 patients said they were satisfied and 5 other patients said they were dissatisfied, 5 patients said they were dissatisfied due to user complaints, including: The application sometimes cannot be used if it is not updated immediately. This study aims to determine patient satisfaction with the quality of online registration for the JKN mobile application based on the dimensions of content, accuracy, format, ease of use, timelines at Godong Community Health Center. The type of research used is quantitative descriptive research. The data collection method uses a questionnaire. The instrument used was a questionnaire. The population and sample in this study were all BPJS Health participants who used the JKN mobile application, namely 226 participants and a sample of 70 respondents. The research results showed that the majority of respondents were satisfied with the quality of registration via the Mobile JKN application. Aspects of ease of use and speed of the registration process receive high ratings from patients [2]. Research shows that from the dimensions of content, 77.1% were satisfied and 18.6% were very satisfied, accuracy was 81.4% satisfied and 14.3% very satisfied, format was 84.3% satisfied and 11.4% very satisfied, ease of use expressed satisfaction 81.4 and very satisfied 14.3%, timelines expressed satisfaction 80% and very satisfied 15.7%.